The fourth option : a thriller - Carr, Jack; Woodward, M. P. (The fourth option series, 2026)
"Disillusioned by the government and institutions he dedicated his life to serving, former Navy SEAL and CIA ground branch operative Chris Walker is about to end his life when he receives a call that saves it. The wife of a teammate he lost in Afghanistan has now lost her son to the opioid crisis and needs Walker's help. Thrust into a conspiracy that goes deeper than he ever imagined, Walker must go upagainst the system and the very Constitution he once swore an oath to support and defend in order to find justice for his friend's widow. With ambitious FBI agent Jarrett Stanton on his tail, Walker-accompanied by his loyal Belgian Malinois and using his off-the-grid VW pop-up camper filled with a hidden cache of weapons-takes the law into his own hands, exposing corruption and issuing a long-forgotten brand of lethal outlaw justice."--Provided by publisher.